(untitled) - Hartmann, Pamela (New York, 1997)
This text combines reading and writing skills in one text. After completing the first parts of any chapter, students will have a firm base of vocabulary, grammar, and ideas needed for completing the writing exercises in Part Four. Ideal for pre-beginning to beginning ESOL students.
Keywords: English language,English language,Listening; Study and teaching,Textbooks for foreign speakers,Problems, exercises, etc